Unsur Menyalahgunakan Kewenangan dalam Tindak Pidana Korupsi sebagai Kompetensi Absolut Peradilan Administrasi - Muhammad Sahlan (Fakultas Hukum Universitas Islam Indonesia, 2016)
The main issue in this research is whether the power abuse in Corruption is still an absolute competence of Corruption Justice or is shifted into the administrative justice in post-regulation of Government Administration Act. This is a research on normative law that is analytical prescriptive through conceptual approach, statute approach, and case approach. The results of the research showed that the concept of the power abuse in the Government Administration Act theoretically and practically is equal with the concept of power abuse in Corruption Eradication Law. Therefore, those two justices attributively have the absolute competence to examine and determine the elements of power abuse in corruption. However, based on the principle of “lex posteriori derogate legi priori”, the authority to examine and determine the element of power abuse in corruption comes to be the absolute competence of Justice Administrative.